Binary logistic analyses on responses of being healthy and unhealthy to positive and negative mindsets in caregivers - Hwang, Ji-Won (Edelweiss Applied Science and Technology, 2025)
This paper is a descriptive research study on self-perceived evaluations of health in caregivers: (1) It starts with questions about whether caregivers with patients think of being healthy just by themselves. These healthy caregivers have positive mindsets and are less stressed than others; (2) Perceived health status (healthy and unhealthy) was evaluated as a response to factors including demographic characteristics, positive psychological capital, and job stress (negative) using binary logistic analysis; (3) 79 individuals from the perceived good health group were compared with 98 from the perceived poor health group, totaling 177 participants. The mean score of positive psychological capital for the perceived good health group was higher than that of the other group (64.0 ± 8.2 : 61.2 ± 8.0). Additionally, the mean score of job stress for the perceived good health group was lower than that of the other group (98.9 ± 11.0 : 102.2 ± 10.7); (4) In this study, the caregiver group that was healthy had higher positive psychological capital and lower job stress than the other group.